Diagnostic ion‐oriented identification and simultaneous quantification of chemical components in Allium chinense G. Don. Issue 23 (30th October 2018) - Qin, Zifei; Lin, Pei; Yao, Zhihong; Chen, Zilin; Yu, Yang; Dai, Yi; He, Xiangjiu; Zhou, Hua; Yao, Xinsheng
Abstract: Allium chinense G. Don, a popular edible condiment with reputation of Ganoderma lucidum in vegetables, exerts significant health effects for treating coronary disease but chemical compounds and corresponding contents still remain unclear. In this study, a total of 80 chemical compounds were detected in Allium chinense extracts based on a summarized fragmentation pattern, of which 32 were unambiguously identified with reference standards. Furthermore, a practical and feasible method was developed and validated for simultaneous quantification of 18 chemical compounds, of which 17 compounds were steroidal saponins, by ultra‐high performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry. In addition, it was known that the contents of quantitative compounds varied significantly among multiple Allium chinense samples. Moreover, chemometric analysis results suggested that chinenoside I, macrostemonoside B, and chinenoside II were the most important markers responsible for poor consistency. Taken altogether, this study would be helpful for the chemical authentication and quality control of Allium chinense samples.